Organizational embeddedness, turnover intentions, and voluntary turnover: The moderating effects of employee demographic characteristics and value orientations - Peltokorpi, Vesa; Allen, David G.; Froese, Fabian (Journal of organizational behavior, 2015)
To explain why some employees who experience high embeddedness contemplate leaving their organizations and others do not, we examined the moderating effects of employee demographic characteristics (age and gender) and value orientations (individualism and risk aversion) between organizational embeddedness and turnover intentions. Turnover intentions were further expected to increase voluntary turnover. Data were collected from 643 full-time employees at three points in time over a 12-month time period in a wide range of organizations in Japan, a relatively low turnover context with little prior embeddedness research. Findings show that gender and risk aversion moderate the relationship between organizational embeddedness and turnover intentions, which in turn predict voluntary turnover.